THE ROLE OF PUZZLES IN DEVELOPING MENTAL ACTIVITY - Khaliqnazarova Maftunakhan Hayatjon kizi (American Journals, 2023)
In this article, how to use riddles to increase children's ingenuity and mental activity, ways to use riddles to eliminate speech defects, and recommendations for parents.
Keywords: folklore, riddle, thinking ability